Analysis of The Determinants For Human Development Acceleration : A Review on Priority-Sector Expenditures and Economic Growth in Regencies and Cities of East Java - Enrico Rizqullah; Susilo (Journal of Development Economic and Social Studies, 2026)
Human resources are a fundamental aset for the development of regions. High of the economic growth hasn’t been able to increase HDI achivements and reduce the gap in HDI conditions in cities/districts of East Jawa, so there is a need for the government to play a role to make policies, especially in spending allocations. Therefore the purpose of this study is to determine and analyze the effect of education spending, health spending, infrastructure spending, and economic growth on the Human Development Index in the cities/districts of East Java. The type of data used in this study is panel data from 38 cities/districts over a period of five years through the panel data regression analysis method. The research results show that health spending, infrastructure spending, economic growth, and fiscal independence rasio have a significant positive effect on the HDI, meanwhile education spending doesnot have a significant effect on the HDI of cities/regencies in East Jawa. Therefore, the importance of regional spending allocation in key sectors to accelerate human development in East Java region.